A Study on Frameworks of Component Integration for Web Applications - Kim, Haeng-Kon; Yang, Hae-Sool; Lee, Roger Y. (Software Engineering Research and Applications, 2006)
As web application systems become increasingly complex to build developers are turning more and more to integrating pre-built components from third party developers into their systems. This use of Commercial Off-The-Shelf (COTS) software components in system construction presents new challenges to web system architects and designers. Web applications are seldom developed in isolation. Frequently there are many projects building, maintaining and evolving the applications, each with its own life cycle of requirements, design and implementation. To gain improvements in productivity and quality across these applications, it is necessary to consider the main element of theses solutions, to abstract them from the individual solutions, and to manage them as a core asset of the organization. The continuing increase of interest in Component Based Development (CBD) signifies the emergence of a new development trend within the Web application industry. This paper describes issues raised when integrating COTS components for web application, outlines strategies for integration, and presents some informal rules we have developed that ease the development and maintenance of such systems.